STAG1 Disease, Central Precocious Puberty, and Bone Fragility—A Case Report - Rebecca-Cristiana Șerban; Andreea-Mădălina Mituț-Velișcu; Andrei Costache; Luminița-Nicoleta Cima; Carmen Niculescu; Aritina Moroșanu; Anca-Lelia Riza; Ioana Streață (Diagnostics)
Background: Previously reported STAG1 gene-related cohesinopathies describe a range of clinical features, typically including intellectual disability (ID), facial dysmorphisms, and limb anomalies. Case presentation: We present the case of an 8-year-old girl with main findings including ID, central precocious puberty (CPP), and bone fragility. Panel genetic testing revealed a pathogenic STAG1 variant, NM_005862.3:c.2116del p.(Asp706Ilefs*15), which can only partially explain the clinical phenotype. Reports of STAG1-related cohesinopathies, including ours, have consistently described developmental and intellectual disabilities. In our case, the etiology of CPP and bone fragility remains unexplained. We discuss the challenges and limitations of current molecular tools in assessing cases with overlapping, apparently unlinked phenotypes, while speculating whether the common occurrence could be explained by STAG1 instead. Conclusions: The clinical spectrum of cohesinopathies is still poorly understood. Complex phenotypes with apparently unrelated clinical features warrant further careful investigation and illustrate the challenges of molecular diagnosis.